Influence of Price Perception, Product Quality, and E-Wom: Improving Brand Image and Purchase Decision - Pratiwi, Putri Chalia; Silitonga, Parlagutan (Journal of Economics, Assets, and Evaluation, 2024)
The purpose of this study is to determine the impact of price perception, product quality, and electronic word-of-mouth (E-Wom) on brand image and purchase decisions at The Originote skin care products. By using a quantitative approach, the population used in this research to the tune of 285 respondents. It consisted of the number of users or potential users using the convenience sampling method. Taking respondents who are available or who happen to be somewhere is a prerequisite for accidental sampling. Structural Equation Modeling (SEM) with the help of SmartPLS software was used in analizing data. The results show that price perception has no impact on brand image, but purchase decisions are positively impacted by price perception. In addition, the quality of the product has a positive and significant influence on the brand image and the purchase decision. E-wom also has a significant impact on Brand Image and Purchase decisions. Furthermore, Brand Image significantly influences Purchase Decisions at The Originote skincare.